2015
DOI: 10.7314/apjcp.2015.16.8.3325
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Expression of Pim-3 Promotes Proliferation and Migration of Ovarian Cancer Cells

Abstract: Pim kinase-3(Pim-3), a member of serine/threonine protein kinases, has been implicated in multiple human cancers and involved in Myc-induced tumorigenesis. However, little is known regarding its expression and biological function in human ovarian cancer. In this study we showed that the clinical significance and biological functions of Pim-3 in ovarian cancer and found that higher Pim-3 mRNA level are detected in ovarian cancer tissues than those in normal ovarian tissues. There are significant correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…These results suggest that PIM kinases may affect OS metastasis. In agreement with this, previous studies have suggested a role for PIM kinases in cell motility and metastasis, for example, PIM1 was able to promote migration in leukemia and prostate cancer cells (48), PIM2 was shown to induce human liver cell malignant transformation and increase the migration rate (49), and PIM3 can promote ovarian cancer cell migration (50). In addition, absence of PIM kinases blocks the process of bone invasion induced by the 3-methylcholanthrene-induced sarcoma in vivo (51).…”
Section: Discussionsupporting
confidence: 87%
“…These results suggest that PIM kinases may affect OS metastasis. In agreement with this, previous studies have suggested a role for PIM kinases in cell motility and metastasis, for example, PIM1 was able to promote migration in leukemia and prostate cancer cells (48), PIM2 was shown to induce human liver cell malignant transformation and increase the migration rate (49), and PIM3 can promote ovarian cancer cell migration (50). In addition, absence of PIM kinases blocks the process of bone invasion induced by the 3-methylcholanthrene-induced sarcoma in vivo (51).…”
Section: Discussionsupporting
confidence: 87%
“…Impaired expression of MACC1 is associated with several malignant tumors. MACC1 down-regulation in OC cells inhibits migration, invasion and proliferation of these cells, and increases the apoptosis [ 11 ]. MACC1 inhibition suppresses the growth and metastatic OC cells in vivo and in vitro.…”
Section: Pim Kinases and Proteins Involved In Cellular Functions Omentioning
confidence: 99%
“…Recently, it has been reported that MACC1 and PIM kinases are correlated to each other and they have similar role. PIM3 and MACC1 [ 11 ] expressions have also been reported higher in OC tissues as compared to other tissues [ 11 ]. However, the mechanism by which PIM3 regulates the MACC1 expression is still unknown.…”
Section: Pim Kinases and Proteins Involved In Cellular Functions Omentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled growth of the tumor would be triggered by these changes. Thirdly, previous research on solid tumors and leukemia 14 , 15 , 17 indicated that Pim-3 expression may have important effects on p53 or on other members of the anti-apoptosis Bcl-2 protein family. As the most important apoptosis-inducing gene in the body, p53 critically influences the mitochondrial and death receptor pathways, which are both important for apoptosis.…”
Section: Discussionmentioning
confidence: 98%